A new combination and new synonym of Anna Pellegr.(Gesneriaceae) - XIONG Xiaokai1, GU Jiangmiao1, WEN Fang2,3, BAI Xinxiang1* (Guangxi Zhiwu)
Since the establishment of Anna Pellegr. in 1930, the taxonomic revisions of this genus have been infrequent. Early publications and revisions of Anna were based on specimens collected by foreign missionaries, which led to problems such as brief or inaccurate descriptions of traits and unclear species definition. When researching publication history, comparing morphology and investigating type locality of Anna ophiorrhizoides(Hemsl.)B. L. Burtt & R. A. Davidson and A. rubidiflora S. Z. He, F. Wen & Y. G. Wei, it was found that Didymocarpus cavaleriei H. Lév. published by H. Léveillé in 1911 and Anna rubidiflora was actually the same species, and Didymocarpus cavaleriei was treated as a synonym of Anna ophiorrhizoides. After comparing the morphological characteristics of multiple populations of A. ophiorrhizoides and A. rubidiflora, it was found that the difference in their morphological characteristics lay in the corolla. It was not appropriate to use differences in corolla color as boundaries for the classificatory units of species. Taking into account the morphological characteristics and geographical distribution characteristics, it was proposed to treat A. rubidiflora as a variety of A. ophiorrhizoides. According to the regulations and suggestions in the 2018 International Code of Nomenclature for Algae, Fungi, and Plants(Shenzhen Code), a new combination and a name at new rank —— A. ophiorrhizoides(Hemsl.)B. L. Burtt & R. A. Davidson var. cavaleriei(H. Lév.)X. X. Bai & F. Wen were proposed, and A. rubidiflora was treated as a synonym of the new combination.